Inward rectifier potassium (Kir) channels in the soybean aphid Aphis glycines: Functional characterization, pharmacology, and toxicology. (October 2018) - Piermarini, Peter M.; Inocente, Edna Alfaro; Acosta, Nuris; Hopkins, Corey R.; Denton, Jerod S.; Michel, Andrew P.
Graphical abstract: Highlights: The genome of Aphis glycines possessed 2 Kir channel genes: ApKir1 and ApKir2. ApKir1 and ApKir2 formed barium-inhibitable Kir channels in Xenopus oocytes. ApKir1 produced larger K + -currents with stronger rectification compared to ApKir2. ApKir1 was more sensitive to barium compared to ApKir2. Small molecule inhibition of Kir channels in vivo was lethal to aphids within 24 h. Abstract: Inward rectifier K + (Kir) channels contribute to a variety of physiological processes in insects and are emerging targets for insecticide development. Previous studies on insect Kir channels have primarily focused on dipteran species (e.g., mosquitoes, fruit flies). Here we identify and functionally characterize Kir channel subunits in a hemipteran insect, the soybean aphid Aphis glycines, which is an economically important insect pest and vector of soybeans. From the transcriptome and genome of Ap. glycines we identified two cDNAs, ApKir1 and ApKir2, encoding Kir subunits that were orthologs of insect Kir1 and Kir2, respectively. Notably, a gene encoding a Kir3 subunit was absent from the transcriptome and genome of Ap. glycines, similar to the pea aphid Acyrthosiphon pisum . Heterologous expression of ApKir1 and ApKir2 in Xenopus laevis oocytes enhanced K + -currents in the plasma membrane; these currents were inhibited by barium and the small molecule VU041. Compared to ApKir2, ApKir1 mediated currents that were larger in magnitude, more sensitive to barium, and less inhibited by small molecule VU041. Moreover, ApKir1 exhibited stronger inward rectification compared to ApKir2. Topical application of VU041 in adult aphids resulted in dose-dependent mortality within 24 h that was more efficacious than flonicamid, an established insecticide also known to inhibit Kir channels. We conclude that despite the apparent loss of Kir3 genes in aphid evolution, Kir channels are important to aphid survival and represent a promising target for the development of new insecticides.